The Relationship between the Number of Major Organ Involvement and Therapeutic Response of Pulse Dose Methylprednisolone in Systemic Lupus Erythematosus Patients - Kartyanto, Adhita; Paramaiswari, Ayu; Kertia, Nyoman (Acta Interna The Journal of Internal Medicine, 2023)
Background. Systemic Lupus Erythematosus (SLE) requires comprehensive and integrated treatment because it can manifest in various organ systems, both non-major and major organs. Pulse doses Methylprednisolone used as induction therapy, it provides dramatic improvement in prognosis in severe lupus through its nongenomic effects. Not all SLE patients who received pulse dose methylprednisolone therapy gives complete response, several factors may influence the therapeutic response, one of which is thought to influence the difference in therapeutic response is the number of major organ involvement.Objectives. To determine the relationship between the number of major organ involvement and therapeutic response of pulse dose methylprednisolone therapy in SLE patients at Dr. Sardjito Hospital Yogyakarta.Methods. This study used a retrospective cross-sectional study. The subjects of this study were adult patients with SLE treated in the internal medicine ward at Dr. Sardjito Hospital Yogyakarta and met the inclusion and exclusion criteria from January 1, 2016 to December 31, 2019. The data on the characteristics of the research subjects were taken from the patient's medical records and laboratory data before giving pulse methylprednisolone.Results. A total of 88 research subjects were taken from medical records. Patients with major organ involvement 1 experienced more complete response (53.8%), major organ involvement 2 mostly partial response (66.7%), major organ involvement 3 (48.6%) and major organ involvement 4 (53.8%) no response, and major organ involvement 5 (75%) partial response. There is a significant relationship with the number of major organ involvement with therapeutic response p<0.001. The correlation coefficient r=0.382 means that the more major organ involvement the less therapeutic response. The results of multivariate analysis showed that only the number of major organ involvement had a dominant effect on the therapeutic response, p=0.001. Regression coefficient 0.797.Conclusion. The number of major organ involvement significantly affects the success of pulse dose methylprednisolone therapy in SLE patients.